2022
DOI: 10.1111/aor.14398
|View full text |Cite
|
Sign up to set email alerts
|

Exercise oscillatory ventilation in patients with advanced heart failure with and without left ventricular assist device

Abstract: Background Exercise oscillatory ventilation (EOV), indicating pathological fluctuations on pulmonary arterial pressure, is associated with mortality in patients with heart failure (HF). Whether left ventricular assist device (LVAD)‐induced ventricular unloading can reverse EOV and may prevent short‐term rehospitalization has not been investigated. Methods We performed a retrospective single‐center in‐ and outpatient analysis of patients with (n = 20, LVAD) and without (n = 27, HF) circulatory support and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A small study comparing exercise performance between patients within two months after LVAD implantation (n = 26) and heart failure patients immediately after recompensation from acute heart failure (n = 30) found comparable VO 2peak , but a trend towards lower OUES in LVAD patients suggesting higher ventilatory efforts in LVAD patients [23]. This is also supported by the observation that EOV, as a surrogate marker for elevated pulmonary artery wedge pressure and ventilatory inefficiency, does not seem to resolve following LVAD implantation [24]. Although we did not detect differences in EOV between the groups, we found that V D /V T was higher in LVAD compared to HFrEF patients illustrating more inefficient ventilation during exercise.…”
Section: Assessment Of the Primary Outcomementioning
confidence: 87%
“…A small study comparing exercise performance between patients within two months after LVAD implantation (n = 26) and heart failure patients immediately after recompensation from acute heart failure (n = 30) found comparable VO 2peak , but a trend towards lower OUES in LVAD patients suggesting higher ventilatory efforts in LVAD patients [23]. This is also supported by the observation that EOV, as a surrogate marker for elevated pulmonary artery wedge pressure and ventilatory inefficiency, does not seem to resolve following LVAD implantation [24]. Although we did not detect differences in EOV between the groups, we found that V D /V T was higher in LVAD compared to HFrEF patients illustrating more inefficient ventilation during exercise.…”
Section: Assessment Of the Primary Outcomementioning
confidence: 87%